Peningkatan Hasil Belajar Fisika Melalui Model Problem Based Learning (PBL) Pada Peserta Didik Smait Iqro Bengkulu - Ismi Adelia; M Farid; Aprizal Mayub (Journal on Education, 2021)
Abstract The purpose research is to find out whether the application of the Problem Based Learning (PBL) model can improve the learning achievement of students Physics Group at SMAIT Iqro Kota Bengkulu. This research is experimental research by using quasi-experimental research with one group pretest-posttest design. Data collection techniques used by collecting the first stage data (pretest), conducting experiments, and collecting the second stage data (posttest). The research results showed that there were three groups of students namely higher, medium, and lower group. The higher group got a high gain value 0.82. The medium group got a gain value 0.75 while the lower group was at the medium criterion with a gain value of 0.56. To determine the differences of learning achievement on the higher, the medium and the lower, the two-way Anova test was used. The conclusion was the application of the PBL model on the concept of Earthquake and Tsunami Intensity can improve the students’ learning achievement who were a Physics Group at SMAIT Iqro Kota Bengkulu.